Rosa Bacile and John McNeill (eds). Romanesque and the Mediterranean, Points of contact across the Latin, Greek and Islamic Worlds, c.1000- c.1250 - Crow, James (Journal of Greek Archaeology, 2016)
This informative and well-presented volume is the result of papers presented in Palermo in 2012 at the British Architectural Association’s second international Romanesque conference. The Romanesque is essentially a Latin, central and western European expression of art and architecture and the papers identify and question those points of contact with the established traditions of Byzantium and Islam. Few places are better placed to see this interaction than Sicily and this is reflected in two of the main papers on the Cappella Palatina, Roger of Sicily’s new Norman palace in Palermo (it should be noted that the papers vary considerably in length). The first by Johns concerns Moslem Fatimid artists of the painted ceiling and how they were influenced by the Byzantine and Romanesque images they encountered in Palermo.